Improving Teacher Pedagogy In the Creation of IT-Based Learning Media - Christina Simanjuntak; Nunuk Hariyati; Endang Purbaningrum (Universitas Yudharta Pasuruan, 2020)
Effective learning using information technology is one of the opportunities that can be utilized by teachers to improve the effectiveness of learning. This study aims to describe the implementation of IT-based learning media creation training to improve teacher pedagogical skills as measured from the practical aspects and effectiveness of the Model used, namely the Critical Event Model (CEM). The subjects of this study were the teachers of SD Santo Yosef Surabaya. This research is an implementation research with quantitative approach. The data collection method used in this research is in the form of questionnaires to assess aspects of practicality and media assessment to assess aspects of effectiveness. The results showed that the training that had been evaluated through media assessment by the trainer and questionnaire scores by participants, both had a high percentage. Based on the results of the research shows that the implementation of training on creating IT-based learning media has been effective and practical